Effectiveness of E-Module Literacy Movement Learning Devices to Increasing Mathematical Concept Understanding Ability - Sumliyah, Sumliyah; Arwanto, Arwanto; Imanudin, Imanudin (Universitas Wiralodra, 2023)
This study aims to determine the effectiveness of the assisted e-module literacy movement learning device software Flipbook Maker html5 type in improving students understanding of mathematical concepts. The background of this research is the low interest in reading, the ability to read and interpret reading and learning in the classroom is more teacher center so that literacy and the ability to understand concepts are rarely trained. This research is a research and development (R&D) method using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This research was conducted at Karya Nasional Sindangwangi Vocational School with research subjects namely class XII students of Motorcycle Engineering Skills Competency. The effectiveness test phase was carried out by students of class XII TSM 2 with a total of 34 students. Data collection techniques using test instruments in the form of questions pretest and posttest then analyzed using descriptive statistics. The results showed that the average value average yield pretest namely 53,82 and the average value of the results posttest ie 82,35. The results of the effectiveness test reached moderate criteria, with a percentage of 62,0483% so that the e-module that had been developed could be said to be